DIFFERENCES OF EATING HABITS CAUSING HIGH SALT INTAKE OBSERVED IN SHIMANE COHRE STUDY. (June 2018) - Isomura, M.; Abe, T.; Nabika, T.
Abstract : Objective: To prevent hypertension, it is important to promote the reduction of salt intake, however, its practice is not easy. One of the reasons for the difficulty is that it will be ineffective unless differences in dietary habits in each region are considered. We conducted estimation of salt intake and eating habits for 2 consecutive years. Design and method: We conducted the survey in 2 areas, one in the middle mountainous area (Town A) and another in isolated island area (Town B)at Shimane prefecture in Japan. We collected spot urine and acquired clinical data such as blood pressure at the annual medical examination. The amount of daily salt intake was estimated from spot urine using Tanaka's method. In addition, dietary habits were surveyed. Results: At Town A, there was no statistical difference in the average daily salt intake in 2014 and 2015, those were 9.67 g and 9.70 g, respectively. Likewise, the average of salt intake of both years showed no difference at Town B. Analysis of relationship between eating habits and salt intake showed that causative eating habits for high salt intake were different between at Town A and B. At town A, the number of times of eating pickles showed high correlation with the amount of salt intake. However, at Town B, there was no correlation between those. Instead, the number of taking miso-soup highly correlated with the amount of salt intake at Town B. However, this trend was not observed in Town A. Conclusions: Although the geographical distance between Town A and B were less than 100 km, eating habits which contribute to high salt intake were different. In Town A, there is a habit to eat pickles at the tea time, suggesting that eating pickles were the most causable habit for high salt intake. However, the number of times to eat pickles per day does not differ between Town A and B. It is suggested that the amount of eaten pickles or salt content may differ. Our study suggested that even in the same regional area, the difference in eating habits should be considered.